Termination of the employment contract by the employee without notice in the light of judicial practice of the Supreme Court - Majchrzak, Katarzyna (Prawo Kanoniczne, 2020)
The article presents issues related to the termination of an employment contract by the employee without notice with particular emphasis on the evolution of views in the jurisprudence of the Supreme Court. The conditions provided for in art. 55 of the Labor Code enable the employee to terminate the employment contract without notice. Attention was also paid to formal requirements and rights of the parties including compensation to which the employee is entitled. The analysis of the institution in question was also enriched with topics related to the employer's claims in the event of an unjustified termination of the employment contract by the employee in the discussed mode